2023
DOI: 10.1111/tid.14070
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, management, and burden of cytomegalovirus in solid organ transplant recipients in selected countries outside of Europe and North America: A systematic review

Abstract: BackgroundCytomegalovirus (CMV) is a frequent infectious complication following solid organ transplantation (SOT). Considering significant differences in healthcare systems, a systematic review was conducted to describe the epidemiology, management, and burden of CMV post‐SOT in selected countries outside of Europe and North America.MethodsMEDLINE, Embase, and Cochrane databases were searched for observational studies in SOT recipients across 15 countries in the regions of Asia, Pacific, and Latin America (sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
(311 reference statements)
0
1
0
Order By: Relevance
“…Silva Junior et al presented a systematic review of the epidemiology, management, and burden of HCMV post-SOT in selected countries outside of Europe and North America in a 10-year period. The authors selected 49 studies out of 2708 studies and reported that rates of HCMV infection within one year were 10.3–63.2% (9 studies) and 0–19.0% (17 studies), up to 4.4% patients were resistant to treatment (3 studies) and no studies reported on refractory HCMV, which proves that rates of HCMV infection/disease post-SOT are highly variable [ 78 ]. A French two-center study included 81 SOT recipients with refractory HCMV infections monitored during a 10-year period and detected 24 genotypic profiles that conferred resistance to GCV and 2 to GCV and CDV.…”
Section: Prevalence Of Hcmv Drug Resistance Worldwidementioning
confidence: 99%
“…Silva Junior et al presented a systematic review of the epidemiology, management, and burden of HCMV post-SOT in selected countries outside of Europe and North America in a 10-year period. The authors selected 49 studies out of 2708 studies and reported that rates of HCMV infection within one year were 10.3–63.2% (9 studies) and 0–19.0% (17 studies), up to 4.4% patients were resistant to treatment (3 studies) and no studies reported on refractory HCMV, which proves that rates of HCMV infection/disease post-SOT are highly variable [ 78 ]. A French two-center study included 81 SOT recipients with refractory HCMV infections monitored during a 10-year period and detected 24 genotypic profiles that conferred resistance to GCV and 2 to GCV and CDV.…”
Section: Prevalence Of Hcmv Drug Resistance Worldwidementioning
confidence: 99%